COMPARISON OF SITA STANDARD 24-2 WITH SITA FASTER 24-2C PROGRAM ON HUMPHREY FIELD ANALYZER IN ASSESSING VISUAL FIELD DEFECTS OF GLAUCOMA PATIENTS: Oral Presentation - Observational Study - Resident - Rianti, Nuzul; Satari, Karmelita; Gustianty, Elsa; Prahasta, Andika; Rifada, R. Maula; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesIntroduction: Periodical perimetry examination to detect and determine the rate of glaucomaprogression continues to be a challenging task, because it depends on many factors. Besides, thereis now a paradigm shift which central visual field defects occur earlier. SITA Standard (SS) 24-2 isthe clinical standard for glaucoma examination, but there were studies reporting on the prevalenceof central visual field defects not detected. SITA Faster (SFR) 24-2C was developed to addresscurrent shortcomings, but the performance has yet to be formally and independently assessed.Objectives: To compare the global indices (Mean Deviation, Pattern Standard Deviation, Visual FieldIndex) and test duration between SS 24-2 and SFR 24-2C program. MethodsThis is an analytical observational study with a cross-sectional design. Subjects aged >18 years whodiagnosed with glaucoma and whose visual fields unaffected by other condition besides glaucomawere included. All subjects underwent testing of both programs. ResultsThis study was conducted in 94 eyes of 66 patients. Comparison of global indices and test durationbetween the two programs was carried out by the Wilcoxon test. The mean results of MD and PSDglobal indices were not significantly different, however there was a difference in the mean VFI of1.5% between the two programs. The test duration of SFR 24-2C was 55.03% faster. ConclusionThere was no significant difference in the MD and PSD global indices, but there was a significantdifference in the VFI, as well as the test duration between the two programs.